Time to clinical investigation for Indigenous and non‐Indigenous Queensland women after a high grade abnormal Pap smear, 2000–2009. Issue 2 (6th February 2017) - Whop, Lisa J; Baade, Peter D; Brotherton, Julia ML; Canfell, Karen; Cunningham, Joan; Gertig, Dorota; Lokuge, Kamalini; Garvey, Gail; Moore, Suzanne P; Diaz, Abbey; O'Connell, Dianne L; Valery, Patricia; et al.
Abstract: Objectives: To investigate time to follow‐up (clinical investigation) for Indigenous and non‐Indigenous women in Queensland after a high grade abnormality (HGA) being detected by Pap smear. Design, setting, participants: Population‐based retrospective cohort analysis of linked data from the Queensland Pap Smear Register (PSR), the Queensland Hospital Admitted Patient Data Collection, and the Queensland Cancer Registry. 34 980 women aged 20–68 years (including 1592 Indigenous women) with their first HGA Pap smear result recorded on the PSR (index smear) during 2000–2009 were included and followed to the end of 2010. Main outcome measures: Time from the index smear to clinical investigation (histology test or cancer diagnosis date), censored at 12 months. Results: The proportion of women who had a clinical investigation within 2 months of a HGA finding was lower for Indigenous (34.1%; 95% CI, 31.8–36.4%) than for non‐Indigenous women (46.5%; 95% CI, 46.0–47.0%; unadjusted incidence rate ratio [IRR], 0.65; 95% CI, 0.60–0.71). This difference remained after adjusting for place of residence, area‐level disadvantage, and age group (adjusted IRR, 0.74; 95% CI, 0.68–0.81). However, Indigenous women who had not been followed up within 2 months were subsequently more likely to have a clinical investigation than non‐Indigenous women (adjusted IRR for 2–4 month interval, 1.21; 95% CI, 1.08–1.36); by 6 months, a similar proportion of Indigenous (62.2%; 95% CI, 59.8–64.6%) and non‐Indigenous women (62.8%; 95% CI, 62.2–63.3%) had been followed up. Conclusions: Prompt follow‐up after a HGA Pap smear finding needs to improve for Indigenous women. Nevertheless, slow follow‐up is a smaller contributor to their higher cervical cancer incidence and mortality than their lower participation in cervical screening.